Effect of Storage Duration on the Stability of Aliquot and Non-Aliquot Commercial Control Serum Levels in Creatinine Examination: Perbedaaan Lama Waktu Penyimpanan Terhadap Stabilitas Kadar Serum Kontrol Komersial Aliquot dan Non Aliquot Dalam Pemeriksaan Kreatinin - Diah Ayu Nuraini; Arifiani Agustin Amalia; Aji Bagus Widyantara (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
The stability of commercial control sera is affected by storage techniques and duration, directly impacting laboratory accuracy. This study aimed to analyze the differences in creatinine stability in control sera stored using aliquot and non-aliquot methods based on storage time. A quasi-experimental approach (one-group pretest-posttest) was applied to control sera stored at 2-4°C and observed on days 0, 5, 7, and 9. Data from 48 tests were evaluated using the Independent Sample T-test. Results indicated an escalation in creatinine levels corresponding to storage duration. The aliquot group increased from an average of 1.36 g/dL to 1.52 g/dL, while the non-aliquot group spiked more sharply from 1.39 g/dL to 1.63 g/dL. Significant instability emerged on the ninth day (p<0.05). In conclusion, the non-aliquot technique triggers more severe deterioration or pseudo-level increases in creatinine compared to the aliquot technique over extended storage periods. Therefore, the use of the aliquot method is highly recommended to maintain the stability of control sera during storage.